2005
DOI: 10.1103/physrevb.71.014506
|View full text |Cite
|
Sign up to set email alerts
|

Origin of anomalous low-temperature downturns in the thermal conductivity of cuprates

Abstract: We show that the anomalous decrease in the thermal conductivity of cuprates below 300 mK, as has been observed recently in several cuprate materials including Pr 2−x Ce x CuO 7−␦ in the field-induced normal state, is due to the thermal decoupling of phonons and electrons in the sample. Upon lowering the temperature, the phonon-electron heat transfer rate decreases and, as a result, a heat current bottleneck develops between the phonons, which can in some cases be primarily responsible for heating the sample, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 17 publications
1
48
0
Order By: Relevance
“…Platelet-shaped samples with typical dimensions ∼ 2 × 0.2 × 0.05 mm 3 were prepared for transport measurements along the [100] direction, using the same four-wire contacts for both electrical and thermal conductivity. Thermal conductivity was measured with a one-heater, two-thermometer steadystate technique and in-situ thermometer calibration in high fields, using low-resistance indium solder contacts to avoid electron-phonon decoupling effects at low temperatures [25,26], and heat currents applied along the [100] crystallographic direction and magnetic field along either [001] or [100], to within 1…”
Section: Pacs Numbersmentioning
confidence: 99%
“…Platelet-shaped samples with typical dimensions ∼ 2 × 0.2 × 0.05 mm 3 were prepared for transport measurements along the [100] direction, using the same four-wire contacts for both electrical and thermal conductivity. Thermal conductivity was measured with a one-heater, two-thermometer steadystate technique and in-situ thermometer calibration in high fields, using low-resistance indium solder contacts to avoid electron-phonon decoupling effects at low temperatures [25,26], and heat currents applied along the [100] crystallographic direction and magnetic field along either [001] or [100], to within 1…”
Section: Pacs Numbersmentioning
confidence: 99%
“…This work does provide a basis for understanding T 2 -dependence in cuprates when it occurs and should be considered when, for example, the magnetic-field dependence of κ is analyzed. A detailed comparison of this work with the low-T data is complicated by the observation of T 3−δ (where δ ≤ 0.3) power laws arising because of a poorly understood boundary-scattering effect 123 and because low-T downturns in κ/T data occur due to heating losses 19 . I shall briefly discuss the doping dependence of these results.…”
mentioning
confidence: 99%
“…For a numerical estimate, I use g ≈ 6 eV obtained from observations of low-T downturns 19 of κ el /T in optimally doped cuprates and assume that g ′ is of the same order 20 as g; the factor in parentheses of Eq. 14 is then of order unity and, introducing the Debye energy ǫ D , k B T 0 ≈ ∆ 0 ǫ D (a/Λ).…”
mentioning
confidence: 99%
“…Smith et al [23] have suggested by phenomenological treatment that the downturn of κ is a result of the decoupling of the heat carrying phonons and electrical charge carriers at low-T , while Hill et al [22] have noted that the downturn is a fundamental intrinsic property of copper oxides. The downturn has been widely accepted as a characteristic of non-Landau Fermi liquid behavior.…”
Section: Resistivity Temperature Upturnmentioning
confidence: 99%
“…The decrease in the density of the conducting carriers is a reason for the MIC of cuprates. It is also the origin of the decoupling of the heat-carrying thermal phonons with these charge carriers [23].…”
Section: B Abdullaev D B Abdullaev C -H Park M M Musakhanovmentioning
confidence: 99%